Mere sexuality : rediscovering the Christian vision of sexuality - Wilson, Todd A., 1976- (Grand Rapids, Michigan : Zondervan, 2017)
"The issues we explore here go beyond questions of same-sex practice, gay marriage, or how to love homosexuals the way Jesus would. We'll touch on a whole range of biblical, theological, cultural, and practical questions related to human sexuality--from birth control and transgenderism to the hook-up culture and theologian Karl Barth's view of the image of God"--Introduction.
Introduction : the road ahead -- What is mere sexuality? -- The sexuality of Jesus -- Male, female, and the Imago Dei -- "One flesh" -- What is sex for? -- Friendship, celibacy, and same-sex relationships -- Homeward bound -- Conclusion : casting vision with joy, tears, and hope -- Appendix 1 : Four core scriptural convictions -- Appendix 2 : Bent sexuality (Joel Willitts).
Includes bibliographical references.
Keywords: Sex -- Religious aspects -- Christianity; Sex -- Biblical teaching